The macroeconomic effects of fiscal policy in Portugal : a Bayesian SVAR analysis - Afonso, António (2018)
With a new quarterly dataset we estimate a Bayesian Structural Autoregression model and a Fully Simultaneous System approach to analyze the macroeconomic effects of fiscal policy. Results show that positive government spending shocks, in general, have a negative effect on real GDP; lead to “crowding-out” effects of private consumption and investment; have a persistent and positive effect on the price level and a mixed impact on the average financing cost of government debt. Explicitly considering the government debt dynamics in the model is also important. A VAR counter- factual exercise confirms that unexpected positive spending shocks create relevant “crowding-out” effects.